Microgramma squamulosa (Kaulf.) de la Sota, Polypodiaceae, como bioindicadora passiva da qualidade do ar - Carvalheiro, César Vinícius (2015)
The urban tropospheric pollution must be monitored, since it may harm human beings and all the living beings. That’s why it is necessary the use of pollution monitoring stations with others complementary methods, such the biomonitoring with plants, which allows the detection of these effects on vegetal beings. The biomonitoring is useful to support a decision related to environmental and health protection. On the above, the aim of this research was to evaluate the bioindicator potential from Microgramma squamulosa (Kaulf.) de la Sota. For this, were made a comparison of the biological alterations (specie abundance, leaf morphometrics, visible symptoms measuraments and mutations by comet assay) and heavy metal determination between different sampling sites from Curitiba, PR, Brazil, with different pollutant emissions characteristics – Central region, Suburban, Industrial and rural. Sterile leaf samples from M. squamulosa were collected at these four points. The results revealed higher genotoxic damages, smaller leaf areas and sclerophylly index at industrial point, whereas the lowest means or absence of DNA damage were observed at rural point. The M. squamulosa abundance were higher at central region, showing a high automotive emissions tolerance, and the lowest abundance were observed at industrial and rural sites. The morphometric analysis shown higher compression from adaxial epidermis and leaf blade at central point, higher stomatal density at industrial point and higher thickness from tissues at rural site, which may be related to a better air quality. The heavy metal analysis revealed higher concentrations at industrial (Zn, Ni) and central (Cu, Pb) sites, and the rural place showed only a high concentration of Mn from agricultural activities. The studied plant do have bioindication potential, being automotive emissions tolerant and less tolerant to industrial emissions.